2023
DOI: 10.48084/etasr.5703
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Classification Accuracy of Four-Class Voluntary-Imagery fNIRS Signals using Convolutional Neural Networks

Abstract: Multiclass functional Near-Infrared Spectroscopy (fNIRS) signal classification has become a convenient way for optical brain-computer interface. fNIRS signal classification with high accuracy is a challenging assignment while the signals are produced by means of voluntary and imagery movements of the same limb. Since the activation in time and space of voluntary and imagery movement show a similar pattern, the classification accuracy by the conventional shallow classifiers cannot reach an acceptable range. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As a result, it is referred to as a False forged. This situation highlights the value of accurate categorization and identification of natural features while also highlighting the limitations of predictive algorithms [16][17][18].…”
Section: B Results On Testing Datamentioning
confidence: 99%
“…As a result, it is referred to as a False forged. This situation highlights the value of accurate categorization and identification of natural features while also highlighting the limitations of predictive algorithms [16][17][18].…”
Section: B Results On Testing Datamentioning
confidence: 99%
“…Huma Hamid et al [38] presented a study to compare the ML classifiers (SVM, K-NN, and LDA) with DL (CNN, LSTM, and Bi-LSTM) algorithms to perform the classification of two classes of walk and rest tasks and reported better performance for DL algorithms. A similar study presented by Mahmudul Haque Milu et al [39] applied ML (support vector machine (SVM) and linear discriminant analysis (LDA)) and compared it with CNN; they reported that CNN performed well in automatic feature extraction as compared to ML. The conventional LSTM algorithm classifies signals based on the input, forget, and output gate mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…The findings of the object detection phase, along with associated information, are subsequently forwarded to the final phase of the model. Within this phase, an integrated proximity detection algorithm [27][28] calculates the distance between recognized objects and the visually impaired user. This model also records nearby objects, along with essential details such as the date and time of identification, during the transition from textual information to voice-based output in the text-to-voice conversion phase [25].…”
Section: Methodology Computer Vision Is An Advanced Technology That O...mentioning
confidence: 99%